IMPLEMENTASI WEBSITE SISTEM INFORMASI PARIWISATA JIMBARAN MENGGUNAKAN METODE SDLC (System Development Life Cycle) - Suharni -; Masimbangan S Harlina; Eel Susilowati; Reiner Franklin Lintjewas (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
Jimbaran has a very interesting tourism potential to explore. The unique natural beauty is still preserved, making it a tourist destination that has its own charm. But, unfortunately at this time the tourist attractions in Jimbaran are still less publicized. Based on the problem, then you need to make a website Jimbaran Tourism Information System that is designed and can be implemented, as a means of conveying information to people who want to know the tourism areas in the region. The designed system can display images, descriptions and location maps as well as videos of tourist objects. The stages to be able to make the design using SDLC (System Development Life Cycle) method, and with the Waterfall model. The design starts from creating a Navigation Structure, Use Case Diagrams, and interface pages. Then the system testing is carried out to find out whether the system is valid or not. Based on the results of testing functions on the system, valid test results obtained. Thus, The system that has been designed can be implemented into an application that can be used by the community as a means of information media about tourism in Jimbaran. Keywords: Website Implementation , SDLC, Information System, Tourist, Jimbaran